Embryology, Anatomy, and Radiology of Cervical Cysts and Cleft Lip/Palate: A Team-Based Learning Module for Medical Students - Janine Prange-Kiel; Julie G. Champine; Alisa J. Winkler; Diane M. Twickler (Association of American Medical Colleges, 2016)
Abstract Introduction Current medical education promotes enhanced integration of various disciplines and early exposure to clinically relevant topics. Against this background, we have developed a team-based learning (TBL) module for medical students in the preclerkship period that integrates embryology, anatomy, and radiology of the head and neck region. Methods The module, which includes prereading assignments, readiness assurance tests, and an application exercise, focuses on the development of the head and neck region. Students were asked to consolidate their knowledge of the topic-acquired as part of their regular curriculum-and to apply this knowledge to cases of cervical cysts and cleft lip/palate. Results The TBL module was developed for a class of 234 students. The students performed well in the TBL module. Although many students perceived the session as time-consuming, the majority of students evaluated it as relevant for their understanding of the course material and a valuable adjunct to their course. Discussion To our knowledge, as of this writing, no TBL modules have been published that focus on the integration of complex embryological topics with anatomy and radiology and that are suitable for medical students at the beginning of their education. Therefore, the presented TBL module fills a gap in material available to educators in the field.